Cancellation Laws/Proof 1

From ProofWiki
Jump to navigation Jump to search

Theorem

Let $G$ be a group.

Let $a, b, c \in G$.


Then the following hold:

Right cancellation law
$b a = c a \implies b = c$
Left cancellation law
$a b = a c \implies b = c$


Proof

Let $a, b, c \in G$ and let $a^{-1}$ be the inverse of $a$.

Suppose $b a = c a$.

Then:

\(\displaystyle \paren {b a} a^{-1}\) \(=\) \(\displaystyle \paren {c a} a^{-1}\)
\(\displaystyle \leadsto \ \ \) \(\displaystyle b \paren {a a^{-1} }\) \(=\) \(\displaystyle c \paren {a a^{-1} }\) Definition of Associative Operation
\(\displaystyle \leadsto \ \ \) \(\displaystyle b e\) \(=\) \(\displaystyle c e\) Definition of Inverse Element
\(\displaystyle \leadsto \ \ \) \(\displaystyle b\) \(=\) \(\displaystyle c\) Definition of Identity Element


Thus, the right cancellation law holds.

The proof of the left cancellation law is analogous.

$\blacksquare$


Sources